UTILIZATION OF FILM GENRE AS PRIOR TEXT STUDY IN TITLE WRITING OF STUDENT CREATIVITY PROGRAM - Nivia Putri Ratna Juwita; Atiqa Sabardila; Markhamah Markhamah (Lire Journal (Journal of Linguistics and Literature), 2020)
This study aims to describe the relationship of intertextuality between the titles of the Student Creativity Program (SCP) with film genres. This research is in the form of qualitative descriptive research that is naturalistic in character. The data source used in this study originates from 5 fields of SCP funded in 2018. Data collection is performed in the form of words, phrases, clauses, and sentences through document study. Observation and note-taking techniques are utilized to collect data. The method of data analysis uses translational identity, referential identity, and abductive inferences. The referential identity method is used to identify the relationship of intertextuality in the writing of the SCP titles and film genres. An intertextual study is carried out comprehensively, by finding similarities and differences between the two. Furthermore, the abductive inferences method is utilized to draw conclusions. The data validity test uses theory triangulation. Based on data analysis, it can be concluded that the relationship of intertextuality contained in the SCP titles involves three film genres: (1) animation; (2) drama; and (3) horror. The results of this study indicate that the use of film genres of animation and drama genres as reference texts has high appeal in the writing of the titles of SCP